PHYSICS OF REMOTE GAMMA THERAPY (Web of Discoveries: Journal of Analysis and Inventions, 2025)
The work presents the physical concept of gamma radiation. The main processes that occur when gamma radiation passes through matter. It shows the advantage of gamma therapy and ways to obtain gamma radiation, as well as the half-life of the isotope, which is the source of gamma radiation.